Joint optimization strategy of service cache and resource allocation in mobile edge network - Long LONG; Zichen LIU; Zaiwang LU; Yucheng ZHANG; Lei LI (Tongxin xuebao)
Aiming at the problem that computing and storage resources of edge node in a mobile edge computing (MEC) system were limited, and excessive task offloading would cause the mismatch between the computing capacity and the load capacity of the edge server, resulting in the increase of task processing delay, the joint optimization of task offloading and storage resources under the three-layer network architecture composed of multi-user, edge server and cloud server was studied to reduce the overall system delay.For the problem was a mixed integer nonlinear problem, a joint optimization strategy of service caching and resource allocation was proposed.First, the continuous and discrete variables of the original problem were decoupled into two sub-problems, namely, the service cache decision problem and the joint optimization problem of computing resources and communication resources.Then, the linear reconstruction, relaxation method and convex optimization method were used to alternately optimize the two sub-problems to obtain the near-optimal solution.Simulation results demonstrate that the proposed strategy can obtain a near-optimal performance with low complexity, and can reduce up to 10% of the task duration compared with other strategies.